2019
DOI: 10.1055/s-0038-1676987
|View full text |Cite
|
Sign up to set email alerts
|

Deep Vein Thrombosis is Modulated by Inflammation Regulated via Sirtuin 1/NF-κB Signalling Pathway in a Rat Model

Abstract: Background Inflammation plays an important role in thrombus formation, and Sirtuin 1 (SIRT1) negatively regulates inflammation via deacetylating nuclear factor-kappa B. However, the relationship between SIRT1-regulated inflammation and deep vein thrombosis (DVT) is still unknown. Objective The aim of this study was to investigate whether SIRT1 plays a critical role in inferior vena cava (IVC) stenosis-induced DVT. Materials and Methods Thrombus weight and histopathologic analysis of IVC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 37 publications
0
18
0
1
Order By: Relevance
“…For example, mice and rats suffering from ischaemia, sepsis, or chronic obstructive pulmonary disease were treated with several natural products including melatonin 76,[87][88][89] , diallyl trisulphide 90 , and punicalagin 86 . Other examples include the effects of ghrelin 82,84 , hydrogen-rich saline 83 , carbon monoxide 62 , the SIRT1 activators resveratrol 67,79,91 and scopolin 92 , and the PARP inhibitor 3aminobenzamide 36 . In all these cases, EX-527 was used as a pharmacological tool to demonstrate that SIRT1 activation was involved in the beneficial effects of the compounds under study.…”
Section: In Vivo Assays Of Ex-527mentioning
confidence: 99%
“…For example, mice and rats suffering from ischaemia, sepsis, or chronic obstructive pulmonary disease were treated with several natural products including melatonin 76,[87][88][89] , diallyl trisulphide 90 , and punicalagin 86 . Other examples include the effects of ghrelin 82,84 , hydrogen-rich saline 83 , carbon monoxide 62 , the SIRT1 activators resveratrol 67,79,91 and scopolin 92 , and the PARP inhibitor 3aminobenzamide 36 . In all these cases, EX-527 was used as a pharmacological tool to demonstrate that SIRT1 activation was involved in the beneficial effects of the compounds under study.…”
Section: In Vivo Assays Of Ex-527mentioning
confidence: 99%
“…EX527 was administered once and was given 20 min before surgery. 26,32 The rats in the normal, sham, and model groups were orally administered with distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…25 Our previous study has shown that DVT is associated with inflammation via SIRT1/NF-kB signaling pathway. 26 Whitmania pigra Whitman (W pigra) is a traditional Chinese medicine (TCM). It was first recorded in Shen Nong's Herbal Classic (Shen Nong Ben Cao Jing) about 2400 y ago and is included in Chinese Pharmacopoeia 2015 edition.…”
Section: Introductionmentioning
confidence: 99%
“…IVC thrombus was induced as described previously [2]. In brief, rats were anesthetized with intraperitoneal injection of 36 mg/kg pentobarbital sodium and then a 2-cm incision was performed along the abdominal midline.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%